The Impact of Industrial Informatization on the Job Market in China (2013 - 2022) - Tao, Xin (2024)
Abstract: This thesis analyzes the impact of Industrial Informatization on China's job market. Based on China's provincial panel data from 2013-2022, it provides an empirical estimation of the effect Industrial Informatization has on employment and labor force skill structure. The results show that: there is a significant positive relationship between Industrial Informatization and China's total employment, i.e. an increase in the level of Industrial Informatization has a significantly positive impact on the total employment. Industrial Informatization is conducive to the change in the skill structure of the employed in manufacturing industry: as the level of informatization increases, the demand for high-skilled and medium-skilled labor in the Chines market increases, and the demand for low-skilled labor decreases. There is a regional heterogeneity in the impact of Industrial Informatization on employment and its labor force skill structure. These results imply that in order to cope with the differentiated impact of Industrial Informatization on employment in manufacturing, the quality of higher education and vocational education should be further improved. The content and mode of skills training should be enhanced, differentiated regional policies should be formulated, and Intelligent Informatization should be actively guided to promote high-quality employment in the manufacturing sector.